Degradação catalítica de polietileno de alta densidade sobre a zeólita HZSM - Lima, Stevie Hallen (2009)
In last years it has talked a lot about the environment and the plastic waste produced and discarded. In last decades, the increasing development of research to obtain fuel from plastic material, by catalytic degradation, it has become a very attractive looking, as these tailings are discarded to millions worldwide. These materials take a long time to degrade themselves by ways said natural and burning it has not demonstrated a viable alternative due to the toxic products produced during combustion. Such products could bring serious consequences to public health and environment. Therefore, the technique of chemical recycling is presented as a suitable alternative, especially since could be obtain fractions of liquid fuels that can be intended to the petrochemical industry. This work aims to propose alternatives to the use of plastic waste in the production of light petrochemical. Zeolites has been widely used in the study of this process due to its peculiar structural properties and its high acidity. In this work was studied the reaction of catalytic degradation of high-density polyethylene (HDPE) in the presence HZSM-12 zeolites with different acid sites concentrations by thermogravimetry and pyrolysis coupled with GC-MS. The samples of the catalysts were mixed with HDPE in the proportion of 50% in mass and submitted to thermogravimetric analyses in several heating rates. The addition of solids with different acid sites concentrations to HDPE, produced a decrease in the temperature of degradation of the polymer proportional the acidity of the catalyst. These qualitative results were complemented by the data of activation energy obtained through the non-isothermal kinetics model proposed by Vyazovkin. The values of Ea when correlated to the data of surface acidity of the catalysts indicated that there is a exponential decrease of the energy of activation in the reaction of catalytic degradation of HDPE, in function of the concentration of acid sites of the materials. These results indicate that the acidity of the catalyst added to the system is one of the most important properties in the reaction of catalytic degradation of polyethylene